The Effect of Recycled CAD/CAM PEEK Fibers on the Transverse Strength of Repaired Acrylic Resin - Maha Kareem Jabbar; Najwah Yousuf Hameed; Rusul Khalid Mustafa (Journal of Techniques, 2023)
One of the significant advantages of Polyether ether ketone (PEEK) is its ability to bond composite materials. This makes it a versatile material that can be used in a range of dental applications, including as a framework for fixed or removable dental prostheses. The aim of this study is to evaluate the transverse strength of heat-cured acrylic resin after reinforcing repaired material with recycled PEEK fibers obtained from a CAD/CAM machine. After milling, PEEK fibers were collected from the CAM machine. The size of the PEEK fibers was measured by utilizing a Scanning Electron Microscope (SEM); with the particle grit size being 200 µm. Thirty specimens were used and divided into three groups of heat-cured acrylic resins was evaluated. All specimens have been stored at 37°C prior to fracture, and specimens have been then repaired after fracture with an auto-polymerizing acrylic resin using Ivomet. Group A of heat-cured specimens was used as a (control group) and repaired with no additive to the self-cured acrylic repair materials. While group B has been repaired by self-cured acrylic reinforced with of 1%wt. PEEK fibers, group C has been repaired by self-cured acrylic reinforced with the addition of 2%wt. PEEK fiber. There is a difference between groups A and C; however, there is a significant difference at 0.05 when comparing with groups B and C. When compared to (1%wt. PEEK-fiber) and the control group, adding (2%wt. PEEK-fiber) improves the transverse strength of the repaired heat-cured acrylic resins.